Fetal micromelia, thoracic dysplasia and polydactyly revisited: A case-based antenatal sonographic approach. (August 2019) - Agarwal, Arjit; Agarwal, Shubhra
Introduction: Skeletal dysplasia is a condition associated with various abnormalities of the skeleton and comprises multiple groups of disorders. Antenatal ultrasonographic assessment of the skeletal dysplasia requires a robust and systematic assessment of the long bones, fetal thorax, skull, spine, pelvis, hands and the feet. Large number of diseases, their overlapping phenotypic features and the lack of systematic approach lead to diagnostic inefficiency. A precise molecular diagnosis also requires an elaborate antenatal sonographic assessment to reach a final diagnosis. Case report: A fetus with micromelia, thoracic dysplasia and polydactyly was detected on prenatal sonography. An algorithmic approach of this rare combination on prenatal sonography is highlighted. Discussion: Fetal micromelia is a relatively common entity which can be subclassified into mild and severe types. The lethal nature of the condition requires assessment of the thoracic biometry which may further narrow down the diagnostic possibilities. The red flags or highlighting features of various conditions like polydactyly, hitch-hiker thumb deformity, ovoid tibia and absent fibula may lead to a specific diagnosis. Conclusion: A background knowledge of various types of micromelia, their lethal nature, associations and specific features of various differential skeletal dysplasia will always be useful, if employed in a systematic manner.